Are There Qualitative Differences in the Representation of Abstract and Concrete Words? Within-Language and Cross-Language Evidence from the Semantic Priming Paradigm. Issue 12 (December 2015) - Ferré, Pilar; Guasch, Marc; García-Chico, Teófilo; Sánchez-Casas, Rosa
The different organizational frameworks theory proposes that there is a qualitative difference between the representation of concrete and abstract words in memory: Concrete concepts would be primarily organized in terms of semantic similarity whereas abstract concepts would be mainly organized by their association with other concepts. Evidence in support of this proposal has been mostly obtained with neuropsychological populations and, to a lesser extent, with healthy participants. In the present work, we tested the different organizational frameworks theory by using, for the first time, a semantic priming paradigm both within language and across languages. The results revealed that there was priming for both semantically similar and associative relations when words were concrete. However, with abstract words, priming was only observed when pairs and targets were associated. These results do not support the proposal of Crutch and coworkers, suggesting that the experimental paradigm as well as the type of relations tested may modulate the pattern of effects obtained with concrete and abstract words.